The Effect of self-disclosure on the quality of friendship in adolescent Army fandom: Pengaruh self-disclosure terhadap kualitas pertemanan pada remaja fandom ARMY - Ade Rahmawati; Zahra Sherina Luthfiya (Psikologia: Jurnal Pemikiran dan Penelitian Psikologi, 2023)
This study aims to determine the influence of self-disclosure on the quality of friendship in adolescent ARMY Fandom. The subjects in this study were 300 ARMY fandom adolescents (aged 18-21 years) who had fellow ARMYs recruited incidentally. The result of this study shows that there is an influence of self-disclosure on quality friendship in adolescent ARMY Fandom.